Fondaparinux em intervenção coronária percutânea no tratamento da síndrome coronária aguda - de Andrade, Pedro Beraldo; Tebet, Marden André; Nogueira, Ederlon Ferreira; de Andrade, Mônica Vieira Athanazio; Barbosa, Robson Alves; Labrunie, André [UNESP]; Mattos, Luiz Alberto (Elsevier, 2012)
Background: Fondaparinux is considered an agent with a well-established safety and efficacy profile in the treatment of non-ST segment elevation acute coronary syndromes, but when used alone, is associated to a higher incidence of thrombotic complications during invasive coronary procedures, requiring the supplementation of an anti-IIa agent. This study aimed to evaluate the efficacy and safety of percutaneous coronary intervention (PCI) in patients with non-ST segment elevation acute coronary syndromes previously treated with fondaparinux. Methods: Prospective, controlled registry enrolling 127 consecutive patients submitted to an early invasive stratification during treatment with fondaparinux, with supplementation of intravenous unfractionated heparin at a dose of 85 U/kg at the time of PCI. Results: The rate of the composite primary endpoint including death, acute myocardial infarction, stroke, stent thrombosis or emergency myocardial revascularization was 3.2%. The cumulative incidence of major bleeding and vascular complications was 3.2%. There were no cases of guidecatheter thrombosis or abrupt vessel closure. Conclusions: PCI in patients with acute coronary syndromes receiving fondaparinux is associated with a low rate of major adverse cardiovascular ischemic events and severe hemorrhagic complications. Supplementation of unfractionated heparin during the invasive procedures eliminates the risk of catheter-related thrombosis.
Fondaparinux in percutaneous coronary intervention for the treatment of acute coronary syndrome
Keywords: Acute coronary syndrome; Angioplasty; Anticoagulants; Fondaparinux; Stents; fondaparinux; heparin; acute coronary syndrome; acute heart infarction; bleeding; catheter thrombosis; clinical trial; death; disease association; drug efficacy; drug safety; emergency care; heart muscle ischemia; human; major clinical study; non st segment elevation acute coronary syndrome; percutaneous coronary intervention; prospective study; revascularization; stent thrombosis; stroke; vascular disease